Magnetically Driven Silver‐Coated Nanocoils for Efficient Bacterial Contact Killing. (29th December 2015) - Hoop, Marcus; Shen, Yang; Chen, Xiang‐Zhong; Mushtaq, Fajer; Iuliano, Loredana M.; Sakar, Mahmut S.; Petruska, Andrew; Loessner, Martin J.; Nelson, Bradley J.; Pané, Salvador
Abstract : The increasing threat of multidrug‐resistant bacterial strains against conventional antibiotic therapies represents a significant worldwide health risk and intensifies the need for novel antibacterial treatments. In this work, an effective strategy to target and kill bacteria using silver‐coated magnetic nanocoils is reported. The coil palladium (Pd) nanostructures are obtained by electrodeposition and selective dealloying, and subsequently coated with nickel (Ni) and silver (Ag) for magnetic manipulation and antibacterial properties, respectively. The efficiency of the nanocoils is tested in the treatment of Gram‐negative Escherichia coli ( E. coli ) and Gram‐positive methicillin‐resistant Staphylococcus aureus ( S. aureus ), both of which represent the leading multidrug‐resistant bacterial pathogens. The nanocoils show highly effective bacterial killing activity at low concentrations and in relatively short durations of treatment time. Three different investigation techniques, LIVE/DEAD assay, colony‐forming unit counting, and scanning electron microscope, reveal that the antibacterial activity is a result of bacterial membrane damage caused by direct contact with the nanocoil. The low cytotoxicity toward fibroblast cells along with the capability of precise magnetic locomotion makes the proposed nanocoil an ideal candidate to combat multidrug‐resistant bacteria in the field of biomedical and environmental applications. Abstract : Antibacterial, silver–coated magnetic nanocoils show high killing efficiency against Gram‐negative and Gram‐positive bacteria by direct contact interaction. Low cytotoxic properties and precise magnetic locomotion make the proposed nanocoil an ideal candidate to combat multidrug resistant bacteria for biomedical and environmental applications.